Occupation-Related Stress among University Faculty Staff in Kwara State, Nigeria: Outcomes on Goal Achievement - Atunde, Martins Olanrewaju; Medupin, Johnson Abiodun; Alabi, Saliu Ishaq; Awarun, Olabode; Oladejobio, Janet Oluwakemi; Oladimeji, Rasheedat Modupe; Maiye, Christiana Abosede (Ushus Journal of Business Management, 2021)
This study examined occupational-related stress among university faculty staff and its implications on goal attainment of universities in Kwara State, Nigeria. The research design was a descriptive research of a cross-sectional survey. Multi-stage sampling technique was used for the selection of 458 faculty staff. Data were collected with the use of 57-item questionnaire. Data collected were analyzed with relevant statistics like percentage, mean, standard deviation, t-test statistics and analysis of variance (ANOVA). Findings revealed that the level of stress among faculty staff was high (3.25), while stress level differs based on gender (p<.05), age (p<.01), marital status (p<.01), work experience (p<.05) and ownership of workplace (p<.05). The prominent risk associated with occupational-related stress were the organizational-related (cluster mean 3.26) and role-related (CM 3.26) factors. Finding further indicated that the social support (CM 3.00) and individual-focused (CM 2.91) coping strategies were moderately adopted for managing occupational-related stress among university faculty, while the organizational support coping strategy was utilized to a low extent (CM 2.47). The findings implicate the attainment of university goals because of the negative effect high-stress level will have on the physiological and behavioural state of faculty staff adding to destructive work and health anomalies.